Cardiac microembolism: prevalence and clinical outcome - Eicke, B.Martin; Barth, Viola; Kukowski, Bornes; Werner, Gerald; Paulus, Walter (Journal of the neurological sciences, 1996)
High intensity transient signals (HITS) have been identified ultrasonically in patients with extracranial vascular or cardiac disease and are suggestive of microembolic material. We studied the prevalence of these signals in 60 patients with increased risk for cardioembolic stroke and in a control group of 20 subjects. Patient groups ( n = 20) were characterized by either non-rheumatic atrial fibrillation (AFIB) (I) or a history of prosthetic valve surgery with AFIB (II) or without AFIB (III). Embolic signals were not seen in the control group. In group I, 3 patients (15%) demonstrated HITS, in groups II and III 10 patients (50%). Microembolic signals in patients with prosthetic heart valves (II, III) had a higher signal intensity, indicating different embolic material. There was no correlation of microembolic signals with the anticoagulant treatment or the position of the prosthetic valve. HITS were found in 1 9 (11%) of the patients with a bioprosthetic valve as compared to 19 31 (61%) with a mechanical valve. After 6–12 months, 1 of 12 HITS positive patients had experienced a stroke and 2 had died. None of the 28 patients without HITS had suffered a stroke, 2 had died. Microembolic signals are frequent events in patients with mechanical prosthetic valves. In these patients they do not appear to be a major prognostic factor for an impending cardioembolic stroke.